POLICY DIRECTIONS FOR OPTIMIZING REGIONAL OWNED BUSINESS ENTITIES MANAGEMENT FOR INCREASING REGIONAL INCOME BASED ON GOOD CORPORATE GOVERNANCE - Bambang Heryanto; Efridani l Lubis; Muhajir MM; slamet riyanto; fauziah fh (El-Arbah: Jurnal Ekonomi, Bisnis Dan Perbankan Syariah, 2022)
Badan Usaha Milik Daerah (Local Government Enterprise/LGE) is appointed to increase locally generated revenue (PAD) refer to Government Regulation No. 54/2017. However, some of those enterprises did not contribute significantly, for example LGE in Kota Bekasi. The root cause of the failure according to Financial Supervisory Agency (BPK) at least due to six factors: (1) governance system, (2) LGE Development Planning has not been well elaborated so that clear to everyone; (3) No clear vision and mission of LGE; (4) no transperancy in staffing recruitment especially for directors and commissioners; (5) low respond for business permit; and (6) lack of capital. Using qualitative method, the study focus on what the key policy for optimalize LGE management to meet statutory order. Using study document supporting with interview, observation, and documentation, the result of the study shows that the key policy is in four aspect, i.e.: (1) good corporate governance arrangement; (2) clear staff recruitment arrangement; (3) clear evaluation procedur; and (4) profit use arrangement. The recommendation based on the study is further study in different local government could be drawing the picture of the problem comprehensively.